PEMBUATAN SISTEM DESAIN RUMAH BERBENTUK 3D MENGGUNAKAN UNITY - Hanif, Irvan Imam; Prasetya, Noven Indra (Informatics Department-Universitas Wijaya Kusuma Surabaya, 2023)
Technology in the field of 3D design is currently developing and is in great demand by millennials. One area that uses 3D design a lot is in the field of advertising and film. Some of the applications used to create this Design System are SketchUp, Blender, and Unity. This study discusses how to create a 3D house design system where the manufacture of this system requires several stages in its completion. The first stage collects some data to understand how to create a 3D design system, the second stage creates objects / spaces that have length, width, and height that have shapes. And also making a GUI (Graphical User Interface) in the form of 2D using Adobe Photoshop Software. After creating a 3D design system object/space and 2D GUI creation, it is hoped that this system can help build a 3D house. From the results of testing the entire system is successful with a percentage of 100% and shows this system can help make 3D house designs. where in the system there is a choice of forms to create 3D designs and tools that can help make home designs.